Simulasi Pola Aliran Pada Bendung Uwai Bangkinang Seberang Kabupaten Kampar - Wahyudi, Rioza; Sujatmoko, Bambang; Mudjiatko, Mudjiatko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Uwai weir which was built on 1938 is located on Bangkinang Seberang, Kampar District. As a result of river containment an inundation area called Embung was formed naturally with nonuniform topography. The distribution of flow velocity is not uniform and causing various flow pattern for every point on Embung Uwai.Flow pattern simulation which is used is qualitative and quantitative. Quantitative simulation based on velocity contour which was generated is divided into return period of 2, 5, and 10 years and by comparing the relation between velocity contour and water depth. Qualitative simulation was observed on water swirl and the flow that occured. The flow pattern generated fom simulation on return period of 2, 5 and 10 years didn’t show any significant different. Flow velocity distribution was compared based on return period of 2, 5, and 10 years. Results obtained was that the highest flow velocity is on section 3 with 0.07 m/s for return period of 2 years, 0.078 m/s for return period of 5 years and 0.08 m/s for return period of 10 years.Keywords : Weir, flow pattern, simulation